Tuning electron donor-acceptor hybrids by alkali metal complexation - Lederer, Marcus; Hahn, Uwe; Fernandez-Ariza, Javier; Trukhina, Olga; Salome Rodriguez-Morgade, M.; Dammann, Claudia; Drewello, Thomas; Torres, Tomas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
A zinc phthalocyanine endowed with four [18]-crown-6 moieties, ZnPcTeCr, has been prepared and self-assembled with either pyridyl-functionalized perylenebisimides (PDI-Py) or fullerenes (C60-Py) to afford a set of novel electron donor-acceptor hybrids. In the case of ZnPcTeCr, aggregation has been circumvented by the addition of potassium or rubidium ions to lead to the formation of monomers and cofacial dimers, respectively. From fluorescence titration experiments, which gave rise to mutual interactions between the electron donors and the acceptors in the excited state, the association constants of the respective ZnPcTeCr monomers and/or dimers with the corresponding electron acceptors were derived. Complementary transient-absorption experiments not only corroborated photoinduced electron transfer from ZnPcTeCr to either PDI-Py or C60-Py within the electron donor-acceptor hybrids, but also the unexpected photoinduced electron transfer within ZnPcTeCr dimers. In the electron donor-acceptor hybrids, the charge-separated-state lifetimes were elucidated to be close to 337 ps and 3.4 ns for the two PDI-Pys, whereas the longest lifetime for the photoactive system that contains C60-Py was calculated to be approximately 5.1 ns.
CRIS-Team Scopus Importer:2023-03-07
Keywords: alkali metals; charge transfer; crown ethers; donor-acceptor systems; fullerenes; perylenbisimides; phthalocyanines